2015
DOI: 10.1093/ofid/ofv158
|View full text |Cite
|
Sign up to set email alerts
|

Global Comparison of Drug Resistance Mutations After First-Line Antiretroviral Therapy Across Human Immunodeficiency Virus-1 Subtypes

Abstract: Background. Human immunodeficiency virus (HIV)-1 drug resistance mutations (DRMs) often accompany treatment failure. Although subtype differences are widely studied, DRM comparisons between subtypes either focus on specific geographic regions or include populations with heterogeneous treatments.Methods. We characterized DRM patterns following first-line failure and their impact on future treatment in a global, multi-subtype reverse-transcriptase sequence dataset. We developed a hierarchical modeling approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Although Manipur has been being one of the hard hit epicenters of the HIV/AIDS epidemic in India since the first detection of HIV-1 in the year 1990, study on drug resistance profile among the HIV infected wives of IDUs of Manipur is limited. Many of HIV/AIDS patients may have been treated inappropriately due to lack of sequence interpretations of newly mutated virus which enhance the viral activity even in presence of antiviral drugs 12 . The surveillance of transmitted and acquired drug resistant strains of HIV-1 is one of the priorities for HIV/AIDS prevention and control.…”
Section: Discussionmentioning
confidence: 99%
“…Although Manipur has been being one of the hard hit epicenters of the HIV/AIDS epidemic in India since the first detection of HIV-1 in the year 1990, study on drug resistance profile among the HIV infected wives of IDUs of Manipur is limited. Many of HIV/AIDS patients may have been treated inappropriately due to lack of sequence interpretations of newly mutated virus which enhance the viral activity even in presence of antiviral drugs 12 . The surveillance of transmitted and acquired drug resistant strains of HIV-1 is one of the priorities for HIV/AIDS prevention and control.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest the preferential selection of certain drug resistance mutations in subtype C ( Loemba et al 2002 ; Brenner et al 2003 , 2006 ; Skhosana et al 2015 ; Huang et al 2016 ) when compared to subtype B, which is the most prevalent genetic form in high-income countries. However, subtype C accounts for approximately 50 per cent of current HIV infections.…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies comparing HIVDR profiles between subtypes in diverse, wellcharacterized cohorts. One such instance is Huang et al's analysis of a multi-cohort, multi-subtype dataset 21 , building upon earlier work by Kantor et al 22 . The latter study found little difference in resistance mutation positions between non-B and subtype B viruses.…”
Section: Introduction/backgroundmentioning
confidence: 99%